Gender representation of 20 years Malaysian films based on Andy Kirk dynamic visualization framework / Nur Naelah ‘Ariefah Nordin and Nasiroh Omar - Nordin, Nur Naelah ‘Ariefah; Omar, Nasiroh (Universiti Teknologi MARA, Perak, 2021)
The role of visualization in journalism evolved when dynamic visualization was introduced. Previously, data visualization in media were constrained with the static nature of the media itself. Nowadays, front-end technology advancement allows for dynamic visualization included in journalism or as a standalone itself. Dynamic visualization ables to provide a compelling story and also effective in summarizing large amounts of data into useful insights. Using Andy Kirk’s framework of creating effective visualization, this paper aims to provide insightful and dynamic visualization on the evolution of Malaysian films in terms of its gender representation, box office success, budget, and genre. About 809 movies produced from the year 2000 until 2020 were sampled and processed prior to being visualized. The visualization shows that while male centric movies have higher box office earnings, female centric movies perform better in relation to their budget, implying that female centric movies can potentially earn better in box office sales if given a higher budget. The paper demonstrates the design, exploration, and implementation processes for an effective dynamic visualization.